A multiwavelength study of star formation in nearby galaxies: evidence for inside-out growth of the stellar disc. Issue 3 (21st July 2022) - Smith, Madison V; van Zee, L; Dale, D A; Hunter, L C; Staudaher, S; Wrock, T
ABSTRACT: Global, radial, and local photometric measurements of several nearby low-mass galaxies are presented. Multiwavelength observations are used to trace the distributions of old and young stars, with the help of far-ultraviolet (FUV) to mid-infrared spectral energy distributions to derive star formation histories (SFHs). In addition to the surface brightness profiles, catalogues of UV-selected sources are created to better understand regions of galaxies with recent star formation. The clustering of these UV sources are studied in the dwarf irregular UGC 08188 (IC 4182) using a two-point correlation function. We find that the reddest of these UV sources are not clustered on any scale, but the bluer sources are clustered on scales approximately less than 1 kpc. We also find a possible negative radial gradient in the SFH parameter that marks the beginning of the younger stellar population's formation ( t burst ) when analysing the entire sample of 3165 UV sources found across a total of 34 galaxies, giving quantitative evidence for the inside-out growth of galactic discs – a natural consequence of galaxy evolution in a Λ cold dark matter universe.